GTP cyclohydrolase deficiency; intrafamilial variation in clinical phenotype, including levodopa responsiveness. Issue 1 (1st January 1999) - Robinson, Richard; McCarthy, Gillian T; Bandmann, Oliver; Dobbie, Michael; Surtees, Robert; Wood, Nicholas W
Abstract : A family with a dominant form of partial GTP cyclohydrolase deficiency is described. Clinical severity varied from mild involvement with complete responsiveness to levodopa to severe dystonia precluding any voluntary activity including talking, progressive contractures, and only partial responsiveness to levodopa. Although there are several possible reasons for intrafamilial variability, any patient with dystonia, the cause of which is not clearly identified, should receive a trial of levodopa.